Pediatric primary pleural synovial sarcoma: A unique case report with brief review of literature - Anant Vatsayan; Ajay Gupta; Sharazad Saab; Agne Petrosiute (Indian Journal of Medical and Paediatric Oncology)
Synovial sarcoma (SS) primary to the pleura is an extremely rare tumor. So far, only nine cases have been reported in pediatric patients. However, none of these patients was found to have a conglomeration of tumors. Here, we report a case of 16-year-old female with monophasic SS and synchronous occurrence of left paraspinal ganglioneuroma and a right paraovarian cystadenoma. A next-generation sequencing genetic panel revealed a novel variant of unknown significance in the MET gene. The occurrence of multiple different tumors in a young patient with a novel genetic variant in a known oncogene (MET) may suggest a possibility of a hitherto unknown cancer predisposition syndrome. We also present a brief review of primary pleural SS reported in pediatric patients.